MENJAGA KEHALALAN DAN KEAMANAN: ANALISIS HUMAN ERROR PROBABILITY PADA PACKING PLANT SEMEN TONASA MENGGUNAKAN METODE SHERPA DAN HEART DI PT BIRINGKASSI RAYA PANGKEP - Sindi Antika; Lamatinulu; Muhammad Nusran (International Journal Mathla’ul Anwar of Halal Issues, 2026)
The implementation of Occupational Health and Safety (OHS) in industrial environments plays a crucial role in minimizing accident risks caused by human error. Based on occupational accident data at PT Biringkassi Raya during 2023–2025, several incidents were still found to result from negligence and non-compliance with Standard Operating Procedures (SOP), particularly in the packing plant area of Semen Tonasa. This study aims to analyze the level of Human Error Probability (HEP) and identify the factors contributing to work errors using the Systematic Human Error Reduction and Prediction Approach (SHERPA) and the Human Error Assessment and Reduction Technique (HEART). The research was conducted through field observations, interviews, and evaluation of SOP compliance across four job positions: packer operator, tender belt operator, jumbo bag worker, and ship loader operator. The SHERPA analysis indicates that the dominant errors are action errors and checking errors influenced by lack of focus, poor communication, and inadequate supervision. HEART calculations show variations in HEP values for each task, with the highest probability found in activities involving the operation and control of heavy equipment. These findings emphasize the need to strengthen SOP supervision, provide regular safety training, and improve workplace communication to reduce human error probability and create a safer, more productive working environment. In addition, safety and halal factors are priorities in activities while in the factory area.